The Combination Effect of Plant Standing and Dosage of Manureon Growth and Years of Corn (Zea Mays L.) Cultivar Sweet Lady - Wijaya, Wijaya; Faqih, Achmad; Ramadhan, Ridwan; Noviana, Nia; Nurjaman, Jajang; Mutiah, Lili (Green Publisher Indonesia, 2023)
This study aims to determine: (1) the effect of the combination treatment spacing and manure dosage on the growth and yield of sweet corn, (2) the best combination of spacing treatment and manure dosage on the growth and yield of sweet corn, and (3) correlation between growth components and yield of sweet corn plants. The experiment was carried out in Bakung Kidul Village, Jamblang District, Cirebon Regency from November 2022 to February 2023. The experimental method used was an experimental method using a Randomized Block Design (RBD) with a further test of the Scott Knott Cluster Test at a 5 percent significance level. It consisted of a combination of spacing and manure treatment, and was repeated three times. The treatment combinations were as follows: A (40 cm x 40 cm and 15 tons of manure/ha), B (40 cm x 40 cm and 20 tons of manure/ha), C (40 cm x 40 cm and 25 tons of fertilizer manure/ha), D (50 cm x 40 cm and 15 tons of manure/ha), E (50 cm x 40 cm and 20 tons of manure/ha), F (50 cm x 40 cm and 25 tons of manure/ ha), G (60 cm x 40 cm and 15 tons of manure/ha), H (60 cm x 40 cm and 20 tons of manure/ha) and I (60 cm x 40 cm and 25 tons of manure/ha). The results showed that: (1) the combination of spacing and manure treatment had a significant effect on the growth and yield of sweet corn, (2) a spacing of 50 cm x 40 cm combined with 20 tons of manure per hectare had the best effect on plant height, number of leaves, cob length, weight of cobs with and without husks per plot. Spacing of 50 cm x 40 cm combined with 20 and 25 tons of manure per hectare gave the best effect on cob diameter, cob weight with and without husks per plant, and (3) there was a significant positive relationship between plant height at 42 days old after planting, the number of leaves aged 28 days and 42 days after planting with cob weight without husk per plot.